A new species of karst forest-adapted Bent-toed Gecko (genus Cyrtodactylus Gray, 1827) belonging to the C. sworderi complex from a threatened karst forest in Perak, Peninsular Malaysia - Grismer, L. Lee; Belabut, Daicus M.; Quah, Evan S. H.; Onn, Chan Kin; Jr., Perry L. Wood (Zootaxa, 2014)
A new species of Bent-toed Gecko Cyrtodactylus guakanthanensis sp. nov. of the C. sworderi complex is described from a limestone forest in Perak, Peninsular Malaysia whose karst formations at the type locality are within an active quarry. Cyrtodactylus guakanthanensis sp. nov. can be distinguished from all other Sundaland species by having the following suite of character states: adult SVL 77.7–82.2 mm; moderately sized, conical, weakly keeled, body tubercles; tubercles present on occiput, nape, and limbs, and extend posteriorly beyond base of tail; 37–44 ventral scales; no transversely enlarged, median, subcaudal scales; proximal subdigital lamellae transversely expanded; 19–21 subdigital lamellae on fourth toe; abrupt transition between posterior and ventral femoral scales; enlarged femoral scales; no femoral or precloacal pores; precloacal groove absent; wide, dark postorbital stripes from each eye extending posteriorly to the anterior margin of the shoulder region thence forming a transverse band across the anterior margin of the shoulder region; and body bearing five (rarely four) wide, bold, dark bands. Destruction of the karst microhabitat and surrounding limestone forest will extirpate this new species from the type locality and perhaps drive it to complete extinction given that it appears to be restricted to the particular microhabitat structure of the type locality and is not widely distributed throughout the karst formations. As with plants and invertebrates, limestone forests are proving to be significant areas of high herpetological endemism and should be afforded special conservation status rather than turned into cement.